GEOCHEMISTRY AND ORIGIN OF THE EASTERN SAYAN OPHIOLITES, TUVA-MONGOLIAN MICROCONTINENT (SOUTHERN SIBERIA) - V. A. Belyaev; K.-L. Wang; M. A. Gornova; S. I. Dril’; A. A. Karimov; A. Ya. Medvedev; Yu. V. Noskova (Геодинамика и тектонофизика)
The Eastern Sayan ophiolites (1020 Ma) of the Tuva-Mongolian microcontinent are believed to be the most ancient ophiolite of the Central Asian Orogenic Belt [Khain et al., 2002].